2022
DOI: 10.1097/mcp.0000000000000890
|View full text |Cite
|
Sign up to set email alerts
|

Emerging phenotypes of pulmonary hypertension associated with COPD: a field guide

Abstract: Purpose of reviewPulmonary hypertension (PH) is a common complication of chronic obstructive lung disease (COPD), but clinical presentation is variable and not always ’proportional’ to the severity of the obstructive disease. This review aims to analyze heterogeneity in clinical features of PH-COPD, providing a guide for diagnosis and management according to phenotypes.Recent findingsRecent works have focused on severe PH in COPD, providing insights into the characteristics of patients with predominantly vascu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 100 publications
0
5
0
Order By: Relevance
“…It has been reported that the presence and severity of PH was strongly associated with the prognosis of COPD [ 28 ]. As early as 1981, it has been proved that the 7-year survival rate of COPD patients with PH was 29.2% compared to 55.6% for COPD without PH [ 29 ].…”
Section: Discussionmentioning
confidence: 99%
“…It has been reported that the presence and severity of PH was strongly associated with the prognosis of COPD [ 28 ]. As early as 1981, it has been proved that the 7-year survival rate of COPD patients with PH was 29.2% compared to 55.6% for COPD without PH [ 29 ].…”
Section: Discussionmentioning
confidence: 99%
“…12 PH is normally identified in later stages of COPD. 13 In literature, different studies have revealed varying degrees of pulmonary hypertension among patients diagnosed with COPD.…”
Section: Discussionmentioning
confidence: 99%
“…In COPD, instead, the relationship between forced expiratory volume in 1 s (FEV 1 ) and mPAP depends on the phenotype. Mild-moderate precapillary PH is common, especially in advanced stages of COPD [75], but severe PH is rare [10] and associated either with low FEV 1 , constituting the little-studied ''severe COPD-severe PH'' phenotype [69], or with mild airflow obstruction in the ''pulmonary vascular phenotype'' [4], where profound hypoxemia may be a better indicator of severe PH than FEV 1 [69].…”
Section: Clinical Presentationmentioning
confidence: 99%
“…Symptoms and sign of right heart failure [67 ▪ ] are frequent in severe PH, although in COPD peripheral edema may exist with preserved right heart function, due to the activation of the renin-angiotensin-aldosterone pathway [68]. Worsening dyspnea, hypoxemia or desaturation on exertion with stable lung function and/or imaging should prompt PH suspicion [67 ▪ ,69]. COPD patients with severe PH experience frequent exacerbations [70], while in IPF this is true even for mild PH [71] (Fig.…”
Section: Clinical Presentationmentioning
confidence: 99%